Modern Mansfield and Old Masters. Hypotyposis in selected short stories by Katherine Mansfield - Kwiatkowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The stories of Mansfield show a strong affinity with seventeenth and eighteenth-century paintings. It is interesting to observe how Mansfield`s Modernist narratives activate in the reader`s mind the pictures and genres typical of past artistic epochs.
Keywords: Mansfield, Katherine (pseud.); Mansfield Murry, Kathleen (1888-1923); still life; vanitas; genre painting; narration